(untitled) (Papeles, 2021)
The Botanical Gardens, as well as having an importance as a means of information and dissemination about the world of plants, are considered opportunities for passive recreation, protection, preservation and conservation of a variety of species, and research in the vegetable field. Considering these aspects, the text is aimed at exposing, succinctly, the origins of these green spaces, their various functions, as well as describing the most prominent Botanical Gardens in Colombia and the world. It is intended to highlight the work and activities that these spaces carry out, in order to motivate their visit and promote an environmental education that favors changes in the behavior and attitudes of students at all school levels.